Uji Most Probable Number (MPN) Bakteri Coliform Pada Jamu Yang Beredar di Pasaran - Kusumastuti, Yulia; Tanjung, Siti Aisyah; Fatimah, Cut; Ayi, Alicia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Herbal Medicine is one of the traditional medicines used since the time of the ancestors until now with ingredients that have not been standardized. jamu has a myriad of benefits for the human body, one of which can maintain body health, prevent disease, maintain fitness and beauty. jamu has two types circulating in the market, namely jamu gendong and jamu kemasan. Processing of jamu gendong which is still done in a simple way with makeshift tools is very likely to cause bacterial contamination. Rich biological resources, especially medicinal plants, can be found in Indonesia. According to research, 90% of Asia's medicinal plants are estimated to be found in Indonesia, with 25% of them-about 7,500 plant species-having been proven effective. In the process of making herbal medicine, it is very important to look at its hygienity, this is because herbal medicine is very easily contaminated by bacteria such as Coliform bacteria, which are indicators of bacterial contamination in general. in this test carried out by the MPN method, the authors are interested in examining the Coliform bacteria mpn test on herbal medicine circulating in the sudirejo village, Medan city. This test sample was carried out using a simple random method on jamu gendong and jamu packaging located in sudirejo Medan. in testing bacterial contamination using Most Probable Number (MPN) with a 3:3:3 tube series with Lactose Broth (BGLB) media and a complete test using Eosin Methylen Blue Agar (EMBA) media, performing gram dye painting and observing microscopic colonies. The results in this study showed that all samples of jamu gendong and packaged jamu (K3) found in the Sudirejo Medan area were contaminated with Coliform bacteria, while the sample of packaged jamu (K6) was not contaminated with Coliform bacteria.